Precision farming and environmental pesticide regulation in the EU—How does it fit together?. (6th June 2022) - Faupel, Michael; von Blanckenhagen, Felix; Lückmann, Johannes; Ruf, Daniel; Wiedemann, Gisela; Ludwigs, Jan‐Dieter
Abstract: Precision farming technology allows pesticides to be applied precisely to the target while leaving the rest of the field untreated. In the regulation of pesticides, however, a homogeneously sprayed field is considered as the standard scenario. To this end, the current status of pesticide risk assessment from the perspective of terrestrial vertebrates, terrestrial invertebrates, and plants as well as aquatic organisms was examined with respect to the EU registration of a pesticide to be applied via precision farming techniques. We highlight which and how respective parts of the technical procedures could be adapted to account for this technology. Our results demonstrate that large parts of risk assessment procedures can be modified, reducing pesticide application and the exposure to the environment. However, further studies and definite procedures are essential to realistically apply, for example, area restriction in the currently required environmental risk assessment schemes. Precision farming has then great potential to achieve the political and public goal of reducing pesticide use, increasing environmental safety, and enhancing the needs of a sustainable agricultural practice. Integr Environ Assess Manag 2023;19:17–23. © 2022 SETAC KEY POINTS: The impact of precise pesticide application (i.e., precision farming) on environmental risk assessment was examined. Based on our findings, precision farming will change the risk assessment procedures, but it can already be partly implemented to current schemes whereas, in other cases, implementation is not currently possible. Potential environmental benefits need to be investigated in more detail, especially regarding community dynamics and recovery patterns.